Geography Environments : VCE Geography Units 1 & 2 - Edited by Furness, Diane (Geography Teachers' Association of Vectoria Inc., 2013)
"Geography Environments has been specifically written to meet the needs of the VCE Geography 2006 Study Design, Units 1 and 2. It incorporates text, case studies, data and activities to help students and teachers develop an understanding of the content and skills of Geography, and to prepare them for success in their VCE assessments. The accompanying Geography Environments CD-ROM contains the entire text in PDF format for electronic use in class or at home."--Back cover.
Include Colour Illustrations, Glossary and Index
Keywords: Victoria